Preparation of 2,3,3-Triarylacrylic Acid Esters Using Suzuki–Miyaura Coupling Reactions - Cardinal, Sébastien; Voyer, Normand (Synthesis, 2016)
We report here a new strategy to produce 2,3,3-triarylacrylic acid esters, a class of 1,2,2-triarylethene compounds with an α,β-unsaturated ester functionality. Our approach requires the preparation of a gem-dibromoalkene precursor from an α-keto ester, followed by the installation of two aryl groups by Suzuki–Miyaura coupling reactions on the two C–Br bonds. Many 2,3,3-triarylacrylic acid esters with one, two, or three different aryl groups were obtained with complete regio- and stereocontrol in most cases.
Keywords: triarylethene; triarylacrylic acid; gem-dibromoalkene; double Suzuki–Miyaura coupling; stereoselective Suzuki–Miyaura coupling